Introduction - Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2014)
This special issue of the journal publishes research papers focusing on new borrowings in Lithuanian. They approach the problem of borrowing from different perspectives: sociolinguistic, morphological, lexicographic, and terminological.
Keywords: none